2016
DOI: 10.3892/ol.2016.5147
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the CHD5 gene and its clinicopathological significance in breast cancer: Correlation with aberrant DNA methylation

Abstract: Abstract. Chromodomain helicase DNA binding protein 5 (CHD5) has been identified as a tumor suppressor in mouse models. Downregulation of CHD5 gene expression is frequently observed in breast cancer cells and tissues. This may be explained by deletions or other mutations; however, alternative mechanisms require investigation. Therefore, the present study evaluated whether CHD5 aberrant methylation has a role in primary breast tumors. A total of 389 patients with primary breast cancer (including 252 paraffin-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…CHD5 gene methylation has been associated with many diseases, so abnormal methylation through the downregulation of CHD5 may cause breast cancer development (Ma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CHD5 gene methylation has been associated with many diseases, so abnormal methylation through the downregulation of CHD5 may cause breast cancer development (Ma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As one of nine members of the CHD family, CHD5 has been con rmed as the tumor suppressor in various malignant tumors. For example, Ma et al reported that the expression of CHD5 was signi cantly suppressed in breast cancer tissues and downregulation of CHD5 may contribute to the development and progression of breast cancer [22]. Liu et al showed that CHD5 mRNA was positively correlated with protein expression and CHD5 gene methylation is associated with clinical and pathological features of colorectal cancer patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…CHD5, also known as DNA binding 5, is a member of the subclass of chromatin remodeling Swi/Snf proteins and is currently considered to be a tumor suppressor (73). The frequency of abnormal DNA methylation of the CHD5 gene promoter is inversely related to the prognosis of patients with cancer and has been observed in several malignancies (74)(75)(76)(77)(78). Despite the limited number of studies, CHD5 promoter methylation has been shown to be associated with OC, suggesting its potential clinical applications in OC metastasis, treatment and prognosis.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%